Understanding the Purchase Behaviour of Turkish Consumers in B2C E-Commerce - Kahraman, Nuri; Tunga, Mehmet Alper; Ayvaz, Serkan; Salman, Yücel Batu (International Journal of Intelligent Systems and Applications in Engineering, 2019)
The significant improvements in communication technologies revealed innovative online services. Time and location barriers have been eliminated and customer satisfaction has gained importance. The most remarkable evolution is observed in electronic commerce. Electronic commerce is a widely accepted industry which provides an effective medium for both retailers and customers, enabling to perform online transactions through websites. The analysis of consumer preferences has become a key aspect in this challenging environment. In this study, the behaviours of Turkish consumers were identified to provide an insight to the practitioners. We examined the moderator effect of consumers' socio-demographic characteristics on online purchasing behaviours. A questionnaire was designed by using the existing literature. A data set of 337 valid records were collected by a questionnaire and analysed by applying association rule mining method. Several interesting rules representing the preferences of online consumers were determined. The results show that the behaviours of Turkish online consumers are related with their demographic characteristics.